POPULARIZING INDONESIAN NEW TERMS OVER COMPETITIVE ACS POPULARISASI ISTILAH BARU DALAM BAHASA INDONESIA DALAM TANTANGAN MEA - Bunga Astya Syafitri; Dian Nurlaili (Proceedings Education and Language International Conference, 2017)
MEA surely give us a broader space, especially in international communication system, yet challenge to deal with. Globally, English is our main connectors and have become real necessity to make an effective communication. It also become more familiar to Indonesian in latest few years and being used by huge number of commercials. In the other side, the popularity of English term goes beyond Bahasa Indonesia, especially for the new terms appeared as the result of development of culture and technology. At the same time, the Indonesian version of terms is not so popular as the English ones. This paper focuses on researching and describing the fact in our surroundings about the unpopular new terms of Indonesian. Also, we will describe the importance of enhancing the using of our own terms, yet suggest to popularize it in many aspect. Keywords: Indonesian language, Indonesian new terms, technology, culture, language sustainability.